Negative electrode material and preparation method and application thereof

By using aromatic compositions to construct a gradient channel for embedded lithium potential difference in lithium ion batteries, the problem of volume expansion and irreversible capacity loss of silicon negative electrode materials during charging and discharging is solved, and higher lithium embedded efficiency and battery capacity are achieved.

CN114975898BActive Publication Date: 2025-03-28BTR NEW MATERIAL GRP CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110193700.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-02-20
Publication Date
2025-03-28
Estimated Expiration
2041-02-20

AI Technical Summary

Technical Problem

The volume of the silicon negative electrode material in lithium-ion batteries expands during charging and discharging, resulting in powderization, irreversible capacity loss and low charging and discharging efficiency, limiting the energy density and cycle life of the battery.

Method used

A lithium source is added to a mixed solution containing an aromatic composition and an organic solvent to form a lithiated solution, and a negative electrode powder material is added to the solution, and a prelithiated negative electrode material is obtained after drying. Different combinations of aromatic compounds are used to construct lithium embedded potential difference gradient channels to improve the embedded depth and efficiency of lithium ions.

Benefits of technology

It effectively improves the lithium embedded depth and lithium embedded efficiency, reduces irreversible capacity loss, and improves the battery capacity and cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114975898B_ABST
    Figure CN114975898B_ABST
Patent Text Reader

Abstract

The present application relates to the field of lithium battery materials, and provides negative electrode materials and preparation methods and applications thereof, the method comprising the following steps: adding a lithium source to a mixed solution containing an aromatic composition and an organic solvent to form a lithiated solution, wherein the lithiated solution comprises a Li-aromatic compound, wherein the aromatic composition comprises at least two aromatic compounds having different R groups; or, the aromatic composition comprises an aromatic compound having an R group and an unmodified aromatic compound; adding a negative electrode powder material to the lithiated solution, and obtaining a pre-lithiated negative electrode material after drying. The negative electrode material for lithium-ion batteries and the preparation method thereof, as well as the lithium-ion battery provided in the present application, can improve the lithium insertion depth and efficiency, reduce irreversible capacity loss, and increase battery capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery materials, and in particular, to negative electrode materials and preparation methods and applications thereof. Background Art

[0002] Lithium-ion batteries are widely used in electric vehicles and consumer electronics due to their advantages such as high energy density, high output power, long cycle life and low environmental pollution. In order to improve the energy density of batteries, the research and development of silicon negative electrode materials are becoming more mature. However, the volume expansion of silicon negative electrode materials is large (>300%) during the process of lithium insertion and extraction. Silicon negative electrode materials will pulverize and fall from the current collector during the charging and discharging process, causing the active material to lose electrical contact with the current collector. The large first irreversible capacity loss consumes a large amount of lithium ions released from the electrolyte and the positive electrode material, resulting in lower charge and discharge efficiency, discharge specific capacity and poor stability, reducing the energy density and cycle life of the battery. Pre-lithiation technology provides an effective solution to solve the irreversible capacity loss and improve the coulombic efficiency.

[0003] Electrochemical pre-lithiation and direct contact short-circuit method are effective and simple ways to mitigate the first irreversible loss of high-capacity carbon materials, alloy negative electrodes and conversion materials. They have the advantages of precise control of pre-lithiation amount and good stability. However, their high requirements for the environment, such as oxygen-free, water-free and dry environment, limit their large-scale application.

[0004] Positive and negative electrode pre-lithiation additives can also be used. However, their compatibility with the electrode preparation process, electrolyte, binder and battery assembly process (its own stability, gas production, toxicity, etc.) during use needs to be further improved.

[0005] On the other hand, chemical pre-lithiation technology has made important research progress in recent years. The use of chemical pre-lithiation technology to prepare pre-lithium-embedded positive and negative electrode materials is a simple and effective method. Since these materials are in an oxidized or reduced state at room temperature, they are easily affected by air, humidity, etc., and large-scale application is also a problem.

[0006] The materials prepared by the above method have limited lithium insertion depth and low initial efficiency, which cannot meet the needs. Summary of the invention

[0007] In view of this, the present application provides a negative electrode material and a preparation method and application thereof, which can improve the lithium insertion depth and lithium insertion efficiency, reduce irreversible capacity loss, and increase battery capacity.

[0008] In a first aspect, an embodiment of the present application provides a method for preparing a negative electrode material, the method comprising the following steps:

[0009] Adding a lithium source to a mixed solution containing an aromatic composition and an organic solvent to form a lithiated solution, wherein the lithiated solution comprises a Li-aromatic compound, wherein the aromatic composition comprises at least two aromatic compounds having different R groups; or, the aromatic composition comprises an aromatic compound having an R group and an unmodified aromatic compound; wherein the R group is selected from at least one of an alkane group, an ether group, a halogen group, an ester group, an amine group and an aromatic group;

[0010] The negative electrode powder material is added into the lithiation solution and dried to obtain the pre-lithiation negative electrode material.

[0011] In the above scheme, by utilizing the synergistic effect between aromatic compounds with R groups in different combinations, or utilizing the synergistic effect between aromatic compounds with R groups and unmodified aromatic compounds, aromatic compounds with different potential difference combinations can construct a lithium insertion potential difference gradient channel, so that the lithium source and the powder material can spontaneously and rapidly chemically insert lithium in an organic solvent, which can effectively improve the lithium insertion depth and efficiency, reduce irreversible capacity loss, and increase battery capacity.

[0012] In one embodiment, the method has at least one of the following features (1) to (6):

[0013] (1) The unmodified aromatic compound comprises at least one of benzene, biphenyl, terphenyl, naphthalene, anthracene, phenanthrene, pyrene and tetracene;

[0014] (2) The alkane group includes at least one of -CH3, -C2H5 and -C3H7;

[0015] (3) The ether group includes at least one of -OCH3, -OCH2CH3 and -OC6H5;

[0016] (4) The halogen includes at least one of -Cl, -F, -Br and -I;

[0017] (5) the ester group comprises at least one of a benzyl ester group and a benzoate ester group;

[0018] (6) The amine group includes at least one of -NH2, -CH2NH2, -CH2CH2NH2, -CH(CH3)NH2, -N(CH3)2, -NHCH2CH3, -NHCH2CH2CH3 and -NHCOCH3.

[0019] In one embodiment, the aromatic composition comprises an aromatic compound having an R group and an unmodified aromatic compound; and the method has at least one of the following features (1) to (4):

[0020] (1) The molar proportion of the aromatic compound having an R group in the aromatic composition is 3% to 97%;

[0021] (2) the molar proportion of the aromatic compound having an alkane group in the aromatic composition is 10% to 90%;

[0022] (3) the molar proportion of the aromatic compound having an ether group in the aromatic composition is 20% to 80%;

[0023] (4) The molar proportion of the halogen-containing aromatic compound in the aromatic composition is 5% to 40%.

[0024] In one embodiment, the aromatic composition comprises at least two aromatic compounds having different R groups, and the aromatic compound combination having different R groups comprises:

[0025] 10% to 80% by mole of an aromatic compound having an alkane group and 20% to 90% by mole of an aromatic compound having an ether group; or

[0026] 60% to 95% by mole of an aromatic compound having an alkane group and 5% to 40% by mole of an aromatic compound having a halogen; or

[0027] The molar proportion of the aromatic compound having an ether group is 60% to 95% and the molar proportion of the aromatic compound having a halogen is 5% to 40%.

[0028] In one embodiment, the method has at least one of the following features (1) to (4):

[0029] (1) The aromatic composition comprises at least two aromatic compounds having different R groups and an unmodified aromatic compound;

[0030] (2) The aromatic composition comprises at least two aromatic compounds having different R groups and an unmodified aromatic compound, and at least one aromatic compound has an alkane group or an amine group;

[0031] (3) the organic solvent comprises at least one of dimethyl ether, dimethyl carbonate, tetrahydrofuran, carbonates, toluene, benzene, ether, propylene oxide and ketone solvents;

[0032] (4) The concentration of the aromatic compound in the mixed solution is 0.2 mol / L to 2.0 mol / L.

[0033] In one embodiment, the method has at least one of the following features (1) to (8):

[0034] (1) The lithium source comprises at least one of lithium metal and a lithium alloy having a lithium content greater than 40%;

[0035] (2) the molar ratio of lithium in the lithium source to the aromatic composition is greater than 2;

[0036] (3) The dissolution time of the lithium source is 5 min to 10 min, and the dissolution temperature of the lithium source is 10° C. to 30° C.;

[0037] (4) The molar ratio of the Li-aromatic compound to the negative electrode powder material is (0.2-2):1;

[0038] (5) The negative electrode powder material includes at least one of a silicon-based material, a carbon-based material and a silicon-carbon composite material;

[0039] (6) The particle size of the negative electrode powder material is less than 50 μm;

[0040] (7) The drying is carried out under a protective gas, wherein the protective gas comprises at least one of helium, neon, argon, krypton and xenon;

[0041] (8) The drying time is 15 min to 60 min.

[0042] A lithium source is added to a mixed solution containing an aromatic composition and an organic solvent to form a lithiated solution, wherein the lithiated solution includes a Li-aromatic compound, wherein the aromatic composition includes an aromatic compound having an alkane group and an aromatic compound having a halogen; silicon dioxide is added to the lithiated solution, filtered after stirring, and washed with an organic solvent, and filtered and dried to obtain a pre-lithiated silicon dioxide material.

[0043] In a second aspect, an embodiment of the present application provides a negative electrode material, which includes nano-silicon, a silicon-oxygen lithium compound and an aromatic compound, wherein the silicon-oxygen lithium compound includes at least one of Li2Si2O5, Li2SiO3 and Li4SiO4, and the aromatic compound at least partially covers the nano-silicon and the silicon-oxygen lithium compound.

[0044] In the above scheme, the negative electrode material for lithium-ion batteries undergoes a pre-lithiation treatment. Since the negative electrode material (silicon oxide material) can embed more lithium ions in the silicon oxide material during the pre-lithiation treatment, the lithium insertion depth and efficiency are improved. During the charge and discharge process, lithium ions will escape from the aromatic compound and enter the silicon oxide material, undergoing an oxidation-reduction reaction and replacing the oxygen in the silicon oxide material, thereby forming some residual alkali on the surface of the silicon oxide material, reducing irreversible capacity loss and increasing battery capacity.

[0045] In conjunction with the second aspect, in a feasible implementation manner, the negative electrode material has at least one of the following characteristics a to e:

[0046] a. The median particle size of the negative electrode material is 4.0um to 8.0um;

[0047] b. The specific surface area of ​​the negative electrode material is 1.5m 2 / g~4.2m 2 / g;

[0048] c. The pH value of the negative electrode material is 10.0 to 11.5;

[0049] d. The negative electrode material further comprises a carbon coating layer;

[0050] e. The negative electrode material further includes a carbon coating layer, and the aromatic compound is distributed on the surface of the nano-silicon particles, in the pores of the carbon coating layer, and on the outer surface of the carbon coating layer.

[0051] In a third aspect, an embodiment of the present application provides an application of a negative electrode material in a lithium-ion battery, wherein the lithium-ion battery comprises a negative electrode plate, a positive electrode plate, a separator and a non-aqueous electrolyte, wherein the negative electrode plate comprises a current collector and a negative electrode material coated on the current collector and prepared according to the pre-lithiation treatment method of the negative electrode material for the lithium-ion battery or the negative electrode material described in the second aspect.

[0052] The technical solution of the present application has at least the following beneficial effects:

[0053] Since aromatic compounds have conjugated π bonds, they can form conjugated compounds of lithium. Through the potential difference between the conjugated compounds of lithium and the material, lithium ions can be embedded deep inside the material. In this scheme, by using aromatic compounds with different potential difference combinations, a lithium insertion potential difference gradient channel can be constructed, so that the lithium source and the powder material can spontaneously and quickly chemically insert lithium in an organic solvent, which can effectively improve the lithium insertion depth and efficiency, reduce irreversible capacity loss, and increase battery capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 A schematic diagram of a process for preparing a negative electrode material provided in an embodiment of the present application. DETAILED DESCRIPTION

[0055] The following is a preferred implementation of the embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the embodiment of the present invention. These improvements and modifications are also considered to be within the scope of protection of the embodiment of the present invention.

[0056] In order to improve the lithium insertion depth and lithium insertion efficiency, reduce irreversible capacity loss, and increase battery capacity, the present application embodiment provides a method for preparing a negative electrode material, such as Figure 1 As shown, the method comprises the following steps:

[0057] Step S10, adding a lithium source to a mixed solution containing an aromatic composition and an organic solvent to form a lithiated solution, wherein the lithiated solution comprises a Li-aromatic compound, wherein the aromatic composition comprises at least two aromatic compounds having different R groups; or, the aromatic composition comprises an aromatic compound having an R group and an unmodified aromatic compound;

[0058] Step S20, adding the negative electrode powder material into the lithiation solution, and obtaining the pre-lithiation negative electrode material after drying.

[0059] In this scheme, by optimizing the R-group modified aromatic composition, the pre-lithium reaction is adjusted to a solid-liquid reaction, the contact surface between the lithium source and the lithium insertion source is increased, and different potential gradients are constructed to change the strength of the π electron cloud and Li binding, thereby improving the lithium insertion efficiency and depth. The aromatic composition is dissolved in an organic solvent system, and the conjugated compound formed by the aromatic compound and metallic lithium is dispersed in the organic solvent, and its electrochemical potential is between the metallic lithium source and silicon dioxide. Through the potential difference between the conjugated compound of lithium and the material, lithium ions can be embedded deep inside the negative electrode material. Therefore, by utilizing aromatic compounds with different potential difference combinations, a lithium insertion potential difference gradient channel can be constructed, and the lithium source and the negative electrode powder material can spontaneously and rapidly chemically insert lithium in an organic solvent, which can effectively improve the lithium insertion depth and efficiency, reduce irreversible capacity loss, and increase battery capacity.

[0060] The unmodified aromatic compound includes at least one of benzene, biphenyl, terphenyl, naphthalene, anthracene, phenanthrene, pyrene and tetracene. Among them, the terphenyl includes at least one of p-terphenyl, m-terphenyl and o-terphenyl.

[0061] The R group is selected from at least one of an alkane group, an ether group, a halogen group, an ester group, an amine group and an aromatic group.

[0062] The alkane group includes at least one of -CH3, -C2H5 and -C3H7. Among them, the propyl group (-C3H7) can be a normal propyl group -CH2CH2CH3 or an isopropyl group -CH(CH3)2.

[0063] The ether group includes at least one of -OCH3, -OCH2CH3 and -OC6H5.

[0064] The halogen includes at least one of -Cl, -F, -Br and -I.

[0065] The ester group includes at least one of a benzyl ester group and a benzoate ester group, specifically but not limited to the following types: HCOOCH2-, -COOCH3, -COOCH(CH3)2.

[0066] The amine group includes at least one of -NH2, -CH2NH2, -CH2CH2NH2, -CH(CH3)NH2, -N(CH3)2, -NHCH2CH3, -NHCH2CH2CH3 and -NHCOCH3. It should be noted that the number of R groups in the aromatic compound is not limited.

[0067] In one embodiment, the aromatic composition comprises an aromatic compound having an R group and an unmodified aromatic compound. In the aromatic composition, the molar proportion of the aromatic compound having an R group is 3% to 97%, and correspondingly, the molar proportion of the unmodified aromatic compound is 3% to 97%.

[0068] Since the potential of unmodified aromatic compounds is too high, the lithium insertion efficiency is low, and the first efficiency of the negative electrode material after pre-lithiation is low; by combining the unmodified aromatic compounds with aromatic compounds having R groups (after modification), adjusting the spatial distribution of the π electron density, constructing the chemical potential gradient difference, and constructing the lithium insertion channel, deep lithium insertion is achieved and the pre-lithiation efficiency is improved, thereby improving the first efficiency of the pre-lithiation material. In a specific implementation method, the chemical reaction intensity between the aromatic composition and lithium can be changed by adjusting the type of R group, thereby promoting the depth of lithium insertion. This solid-liquid chemical pre-lithiation has low heat generation and mild reaction, is suitable for powders or pole pieces, and has good pre-lithiation effect.

[0069] Compared with single R-group aromatic compounds, the combination of R-group aromatic compounds with unmodified aromatic compounds has obvious differences in the composite organic system under low lithium concentration, which is significantly improved compared with single R-group aromatic compounds, reduces the amount of metallic lithium used, reduces production costs, and can also improve the pre-lithium effect of powdered silicon oxide.

[0070] Optionally, the molar proportion of the aromatic compound having an alkane group in the aromatic composition is 10% to 90%, specifically 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or 90%, and of course it can be set according to actual conditions, which is not limited here. Correspondingly, the molar proportion of the unmodified aromatic compound is 10% to 90%.

[0071] The molar proportion of the aromatic compound having an ether group in the aromatic composition is 20% to 80%, specifically 20%, 30%, 40%, 50%, 60%, 70% or 80%, and of course it can be set according to the actual situation, which is not limited here. Correspondingly, the molar proportion of the unmodified aromatic compound is 20% to 80%.

[0072] The molar proportion of the aromatic compound with halogen in the aromatic composition is 5% to 40%, specifically 5%, 10%, 15%, 20%, 25%, 30%, 35% or 40%, and of course it can be set according to the actual situation, which is not limited here. Correspondingly, the molar proportion of the unmodified aromatic compound is 60% to 95%.

[0073] In another embodiment, the aromatic composition includes at least two aromatic compounds with different R groups; the combination of aromatic compounds with different R groups can specifically be:

[0074] 10% to 80% by mole of an aromatic compound having an alkane group and 20% to 90% by mole of an aromatic compound having an ether group; or

[0075] 60% to 95% by mole of an aromatic compound having an alkane group and 5% to 40% by mole of an aromatic compound having a halogen group; or

[0076] The molar proportion of the aromatic compound having an ether group is 60% to 95% and the molar proportion of the aromatic compound having a halogen is 5% to 40%.

[0077] In some embodiments, the aromatic composition includes at least two aromatic compounds having different R groups and an unmodified aromatic compound.

[0078] In some embodiments, the aromatic composition includes at least two aromatic compounds with different R groups and unmodified aromatic compounds, and at least one aromatic compound has an alkane group or an amine group. The more aromatic compound combinations there are, the smaller the restrictions on molar matching, because the subdivision of the potential gradient subdivides the energy level after the hybridization of the electron orbit, the energy barrier of the electron transition transfer is reduced, and the lithium insertion efficiency is improved.

[0079] It should be noted that the molar proportion here refers to the molar proportion of aromatic compounds with a certain type of R group in all aromatic compounds with different R groups. Of course, it can also be a combination of aromatic compounds with an alkane group A and an alkane group B, or a combination of aromatic compounds with an ether group C and an ether group D. It is not limited here.

[0080] Specifically, the potential of the aromatic compound modified with an alkane group or an ether group is lower than that of the aromatic compound modified with a halogen group. Therefore, the molar proportion of the high-potential aromatic compound with a halogen group is set to be less than the molar proportion of the aromatic compound with an ether group or an alkane group. Among them, the potential fluctuation range of aromatic compounds with different ether groups is large, and the combination of aromatic compounds with ether groups and alkane aromatic compounds with lower potential can have a larger potential adjustment space.

[0081] It should be noted that aromatic compounds with alkane groups, aromatic compounds with ether groups, aromatic compounds with halogens, and aromatic compounds containing the above-mentioned R groups have different lithium potentials and potential differences due to the differences in R groups. The potential gradient and lithium insertion channel are constructed on this basis, which is beneficial to improving the lithium insertion efficiency.

[0082] In this scheme, by selecting and combining aromatic hydrocarbon compounds modified by halogen, alkane, ether, lipid, amine, etc., it is possible to change the distribution of π-conjugated electrons while affecting the lithium complex structure and position to construct a chemical lithium insertion channel; it is also possible to avoid the reaction of metallic lithium with the R group, such as lithium reacting with hydroxyl or carboxyl groups to produce hydrogen.

[0083] The preparation method is explained in detail below:

[0084] Step S10, adding a lithium source to a mixed solution containing an aromatic composition and an organic solvent to form a lithiated solution, wherein the lithiated solution comprises a Li-aromatic compound, wherein the aromatic composition comprises at least two aromatic compounds having different R groups; or, the aromatic composition comprises an aromatic compound having an R group and an unmodified aromatic compound;

[0085] In a specific embodiment, the organic solvent includes at least one of dimethyl ether, dimethyl carbonate, tetrahydrofuran, carbonates, toluene, benzene, ether, propylene oxide and ketone solvents.

[0086] The mixed solution may be stirred during preparation to improve the uniformity of the solution, and the stirring method includes at least one of magnetic stirring, ultrasonic stirring and mechanical stirring.

[0087] The concentration of the aromatic compound in the mixed solution is 0.2 mol / L to 2.0 mol / L, specifically 0.2 mol / L, 0.4 mol / L, 0.6 mol / L, 0.8 mol / L, 1.2 mol / L, 1.5 mol / L or 2.0 mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0088] It can be understood that, compared with single-component aromatic compounds, in order to improve the pre-lithiation efficiency, the concentration of aromatic compounds in the pre-lithiation solution is required to be high and the consumption of aromatic compounds is large; and the use of the aromatic composition ratio of the present application can effectively reduce the concentration of aromatic compounds, thereby reducing the loss of aromatic compounds during the pre-lithiation treatment of the material and reducing the pre-lithiation cost.

[0089] After the lithium source is added to the mixed solution, two reactions occur. First, the metal lithium source (solid phase) reacts with the aromatic compound (liquid phase) in the mixed solution to form a metal complex (Li-aromatic compound), so that the metal Li is dissolved in the organic solvent to become a liquid lithium source. Second, the aromatic compound (Li-aromatic compound) after lithium insertion has multiple potential gradients due to different R group modifications, which can effectively reduce the difficulty of Li migration, maintain the lithium concentration near the interface in the pre-lithiation SiO reaction, and achieve efficient and deep lithium insertion.

[0090] In a specific embodiment, the lithium source includes at least one of lithium metal and a lithium alloy having a lithium content greater than 40%;

[0091] The molar ratio of the lithium source to the aromatic compound is greater than or equal to 4; the ratio can be 4, 5, 6, 7, etc. It can be understood that the molar ratio of the lithium source to the aromatic compound is greater than or equal to 4, which can ensure that the lithium source is excessive, so that the metal complex (Li-aromatic compound) can quickly reach a saturated state in the lithiated solution; thereby ensuring that the material that needs pre-lithiation treatment can achieve the target first effect, fully pre-lithiate, and improve efficiency.

[0092] The lithium source is dissolved in the mixed solution. In a specific embodiment, the dissolution time of the lithium source is 5 min to 10 min, specifically 5 min, 6 min, 7 min, 8 min, 9 min, 10 min. The dissolution temperature of the lithium source is room temperature, 10°C to 30°C, specifically 10°C, 15°C, 20°C, 25°C or 30°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0093] It should be noted that within the dissolution temperature range, the organic solvent and the organic compound should be in a liquid mixed state.

[0094] Optionally, after the lithium source is added to the mixed solution, it can also be stirred appropriately so that the lithium source and the mixed solution are mixed more evenly, and the added powder material can be more evenly pre-lithiated on the surface.

[0095] Step S20, adding the negative electrode powder material into the lithiation solution, and obtaining the pre-lithiation negative electrode material after drying.

[0096] It can be understood that the liquid phase lithiation solution contains Li-aromatic compounds, which can maximize the reaction interface of the powder material, increase the reaction area, and reduce the transmission resistance of lithium ions; during the lithiation reaction, LI + It will escape from the aromatic compound and enter the powder material to undergo a redox reaction. The pre-lithium reaction efficiency of the powder material can be regulated by using Li-aromatic compounds with different potential differences to achieve deep lithium insertion.

[0097] In a specific embodiment, the negative electrode powder material includes at least one of a carbon-based material, a silicon-based material, and a silicon-carbon composite material. Specifically, the carbon-based material can be graphite, the silicon-based material can be silicon oxide, silicon element, silicon monoxide, and the silicon-carbon composite material can be SiOx@C, Si@C, and the like. Specifically, when the negative electrode powder material is SiO@C, after the Li-aromatic compound is immersed in the carbon layer, the lithium source undergoes a lithium insertion reaction, and at the same time, the aromatic compound will be partially deposited on the surface of the inner silicon particles, the microporous channels in the carbon layer, and the outer surface of the carbon layer to form an aromatic compound accumulation layer, and an organic polymer crystal layer will be formed in the channel after the solvent is evaporated. When the organic polymer crystal layer is formed, a large amount of conjugated Li source is wrapped. Therefore, during the formation process, these accumulated organic lithium compounds will become part of the SEI layer, reducing the consumption of other active lithium, thereby reducing the loss of the first effect during the formation process and improving efficiency.

[0098] In other embodiments, silicon iodide is added to the lithiated solution, stirred and filtered, and washed with an organic solvent, filtered and dried to obtain a pre-lithiated silicon iodide material.

[0099] When the negative electrode powder material is SiO, the lithium embedding process will be deeper, embed more lithium, and form a dense organic layer on the surface. When the carbon layer is coated later, the high temperature will carbonize this part of the organic layer, forming a carbon layer with special functional groups and doping elements distributed inside. These doping elements can achieve atomic-level dispersion and improve the conductivity of the carbon layer.

[0100] The molar ratio of the lithium source to the negative electrode powder material is greater than or equal to 2; the ratio can be 2, 3, 4, 5, 6, 7, etc. It can be understood that the molar ratio of the lithium source to the negative electrode powder material is greater than or equal to 2, which can ensure that the lithium source is excessive, so that the metal complex (Li-aromatic compound) can quickly reach a saturated state in the lithiated solution; thereby ensuring that the negative electrode powder material that needs pre-lithiation treatment can achieve the target first effect, fully pre-lithiate, and improve efficiency.

[0101] The median particle size of the negative electrode powder material is less than 50um, and can specifically be 1nm, 3nm, 5nm, 10nm, 50nm, 0.1um, 1um, 10um, 20um, 30um or 40um, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. The larger the particle size, the lower the specific surface area and the lower the lithium insertion efficiency. On the basis of ensuring a certain lithium insertion efficiency, by selecting the aromatic composition ratio provided in this application, the applicable range of the powder particle size can be expanded. The smaller the median particle size of the negative electrode powder material, the better, but considering the process cost, preferably, the median particle size of the negative electrode powder material is 1nm to 10nm.

[0102] The molar ratio of the Li-aromatic compound to the negative electrode powder material is (0.2-2):1, specifically 0.2:1, 0.4:1, 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 1.8:1 or 2:1, etc., so as to achieve high-efficiency pre-lithium treatment at a relatively low ratio. At a low concentration ratio, for example, the molar ratio of the Li-aromatic compound to the negative electrode powder material is 0.46, and the first efficiency of the negative electrode powder material after pre-lithium can reach more than 90% in a short time (30 minutes), which significantly improves the pre-lithium efficiency of the negative electrode powder material.

[0103] In some embodiments, the negative electrode powder material is added to the lithiation solution and then stirred, and the stirring method includes at least one of magnetic stirring, ultrasonic stirring and mechanical stirring;

[0104] The stirring time is 15min to 60min, specifically 15min, 20min, 25min, 30min, 35min, 40min, 45min, 50min, 55min or 60min, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable. In a specific embodiment, the corresponding stirring reaction time can be selected according to the ratio of the aromatic composition. Generally speaking, the longer the stirring time, the more complete the reaction, which is conducive to achieving the limit pre-lithium amount that can be achieved by the aromatic composition formula, so that the material can achieve the target first effect.

[0105] After stirring, the mixture is filtered and washed with an organic solvent; the organic solvent used for washing may include at least one of ethanol, ethylene glycol, dimethyl ether, dimethyl carbonate, tetrahydrofuran, carbonates, toluene, benzene, ether, propylene oxide, and ketone solvents.

[0106] The drying is performed under a protective gas, and the protective gas includes at least one of helium, neon, argon, krypton and xenon.

[0107] The drying time is 15 min to 60 min, specifically 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, etc. Drying treatment is beneficial to volatilize the solvent on the surface of the material. Considering the volatilization rate of the solvent, the drying time can be controlled within the above range, which is beneficial to improve the preparation efficiency.

[0108] Optionally, natural air drying is performed in a glove box at room temperature and pressure under argon protection, and the O2 content in the glove box is less than 0.1 ppm, and the H2O content is less than 0.01 ppm.

[0109] Alternatively, dry argon gas is used to purge the powder material for 10 to 30 minutes to completely volatilize the organic solvent adhering to the surface of the material to obtain a dry pre-lithium powder.

[0110] An embodiment of the present invention also provides a negative electrode material, which includes nano-silicon, a silicon-oxygen lithium compound and an aromatic compound, wherein the silicon-oxygen lithium compound includes at least one of Li2Si2O5, Li2SiO3 and Li4SiO4, and the aromatic compound at least partially covers the nano-silicon and the silicon-oxygen lithium compound.

[0111] In the above scheme, the negative electrode material undergoes a pre-lithiation treatment. During the pre-lithiation treatment, more lithium ions can be embedded in the silicon oxide negative electrode material, thereby improving the lithium embedding depth and efficiency. During the charge and discharge process, lithium ions will escape from the aromatic compound and enter the silicon oxide material, undergoing an oxidation-reduction reaction, displacing the oxygen in the silicon oxide negative electrode material, and forming some residual alkali on the surface of the silicon oxide material, thereby improving the material's water system processing performance, reducing irreversible capacity loss, and increasing the battery capacity.

[0112] As an optional technical solution of the present application, the median particle size of the negative electrode material is 4.0um to 8.0um; specifically, it can be 4.0um, 5.0um, 6.0um, 7.0um or 8.0um, which is not limited here. The average particle size of the negative electrode material is controlled within the above range, which is conducive to improving the cycle performance of the negative electrode material.

[0113] In some embodiments, the specific surface area of ​​the negative electrode material is 1.5 m 2 / g~4.2m 2 / g; specifically, it can be 1.5m 2 / g, 1.8m 2 / g, 2.0m 2 / g, 2.5m 2 / g, 3.0m 2 / g, 3.5m 2 / g, 4.0m 2 / g or 4.2m 2 The specific surface area of ​​the negative electrode material is controlled within the above range, which is beneficial to the improvement of the cycle performance of the negative electrode material.

[0114] In some embodiments, the pH value of the negative electrode material is 10.0 to 11.5. The pH value may be 10.0, 10.1, 10.2, 10.3, 10.4, 10.5, 10.6, 10.8, 11.0, 11.2 or 11.5, etc. It can be understood that the material can be kept at a relatively low alkalinity, the water system processing performance of the material can be improved, and the first effect of the negative electrode material can be improved.

[0115] In some embodiments, the negative electrode material further includes a carbon coating layer.

[0116] In some embodiments, the negative electrode material further includes a carbon coating layer, and the aromatic compound is distributed on the surface of the nano-silicon particles, in the pores of the carbon coating layer, and on the outer surface of the carbon coating layer.

[0117] The embodiment of the present invention further provides an application of a negative electrode material in a lithium ion battery, wherein the negative electrode material is prepared by the pre-lithiation treatment method for the negative electrode material for a lithium ion battery provided by the above embodiment of the present invention.

[0118] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. Within the scope of protection, appropriate changes can be made to the implementation.

[0119] Embodiment 1:

[0120] 1) mixing benzophenone (BP), dimethylbiphenyl (4,4-DMBP) and 4,4-difluorobenzophenone (4,4-DFBP) in a molar ratio of 1:1:1 to obtain an aromatic composition, dissolving 0.1 mol of the aromatic composition in 200 ml of dimethyl ether (DME), and treating with magnetic stirring for 30 min to obtain a mixed solution;

[0121] 2) adding 0.45 mol of lithium flakes with a lithium content greater than 99.5% to the mixed solution, and allowing the solution to stand for 10 min to allow the lithium to fully dissolve to form a lithiated solution with a concentration of 0.5 mol / L;

[0122] 3) 10 g of SiO powder (0.22 mol) was added to 200 ml of the lithiation solution and treated by magnetic stirring for 30 min (experimental group 1) and 60 min (experimental group 2). After filtration, the solution was repeatedly washed with anhydrous ethanol for 3 times. After filtration, the solution was placed in a glove box for natural evaporation and drying for 30 min to obtain pre-lithiation SiO powder, which was recorded as S1 and S11.

[0123] Embodiment 2:

[0124] The difference from Example 1 is that benzophenone (BP), dimethylbiphenyl (4,4-DMBP) and 4,4-difluorobenzophenone (4,4-DFBP) are mixed in a molar ratio of 1:2:1 to obtain an aromatic composition.

[0125] The obtained pre-lithiated SiO powders are denoted as S2 and S12.

[0126] Embodiment 3:

[0127] The difference from Example 1 is that dimethylbiphenyl (4,4-DMBP) and 4,4-difluorobenzophenone (4,4-DFBP) are mixed in a molar ratio of 1:1 to obtain an aromatic composition.

[0128] The obtained pre-lithiated SiO powders are denoted as S3 and S13.

[0129] Embodiment 4:

[0130] The difference from Example 1 is that benzophenone (BP) and 4,4-difluorobenzophenone (4,4-DFBP) are mixed at a molar ratio of 1:1 to obtain an aromatic composition.

[0131] The obtained pre-lithiated SiO powders are denoted as S4 and S14.

[0132] Embodiment 5:

[0133] The difference from Example 1 is that benzophenone (BP) and 4,4-difluorobenzophenone (4,4-DFBP) are mixed at a molar ratio of 2:1 to obtain an aromatic composition.

[0134] The obtained pre-lithiated SiO powders are denoted as S5 and S15.

[0135] Embodiment 6:

[0136] The difference from Example 1 is that benzophenone (BP), anisole and 3-fluoroanisole are mixed in a molar ratio of 1:1:1 to obtain an aromatic composition.

[0137] The obtained pre-lithiated SiO powders are denoted as S6 and S16.

[0138] Embodiment 7:

[0139] The difference from Example 1 is that benzophenone (BP), anisole and diphenyl ether are mixed in a molar ratio of 1:1:1 to obtain an aromatic composition.

[0140] The obtained pre-lithiated SiO powders are denoted as S7 and S17.

[0141] Embodiment 8:

[0142] The difference from Example 1 is that benzophenone (BP) and anisole are mixed in a molar ratio of 1:1 to obtain an aromatic composition.

[0143] The obtained pre-lithiated SiO powders are denoted as S8 and S18.

[0144] Embodiment 9:

[0145] The difference from Example 1 is that benzophenone (BP) and 3-fluoroanisole are mixed in a molar ratio of 1:1 to obtain an aromatic composition.

[0146] The obtained pre-lithiated SiO powders are denoted as S9 and S19.

[0147] Embodiment 10:

[0148] The difference from Example 1 is that benzophenone (BP), dimethylbiphenyl (4,4-DMBP) and 4,4-difluorobenzophenone (4,4-DFBP) are mixed in a molar ratio of 1:1:1 to obtain an aromatic composition, 0.1 mol of the aromatic composition is dissolved in 200 ml of a mixed solvent of ethyl cellulose (EC) and dimethyl carbonate (DMC), and the molar ratio of EC:DMC is 1:1, and the mixture is treated with magnetic stirring for 30 minutes to obtain a mixed solution.

[0149] 2) adding 0.45 mol of lithium flakes with a lithium content greater than 99.5% to the mixed solution, and allowing the solution to stand for 10 min to allow the lithium to fully dissolve to form a lithiated solution with a concentration of 0.5 mol / L;

[0150] 3) 10 g of SiO powder (0.22 mol) was added to 200 ml of the lithiation solution and treated by magnetic stirring for 30 min (experimental group 1) and 60 min (experimental group 2). After filtration, the solution was repeatedly washed with anhydrous ethanol for 3 times. After filtration, the solution was placed in a glove box for natural evaporation and drying for 30 min to obtain pre-lithiation SiO powder, which was recorded as S10 and S20.

[0151] Embodiment 11:

[0152] The difference from Example 1 is that benzophenone (BP), dimethylbiphenyl (4,4-DMBP) and biphenyl are mixed in a molar ratio of 1:1:1 to obtain an aromatic composition.

[0153] The obtained pre-lithiated SiO powders are denoted as S11 and S21.

[0154] Embodiment 12:

[0155] The difference from Example 1 is that dimethylbiphenyl (4,4-DMBP) and biphenyl are mixed in a molar ratio of 1:1 to obtain an aromatic composition.

[0156] The obtained pre-lithiated SiO powders are denoted as S12 and S22.

[0157] Comparative Example 1:

[0158] 1) 10 g of SiO powder (0.22 mol) and 3.15 g of Li (0.45 mol) were mixed to obtain a mixture;

[0159] 2) adding 200 ml of a mixed solvent of ethyl cellulose (EC) and dimethyl carbonate (DMC) to the mixture, wherein the molar ratio of EC:DMC is 1:1;

[0160] 3) The samples were treated with magnetic stirring for 30 min (experimental group 1) and 60 min (experimental group 2), respectively. After filtration, they were repeatedly washed with anhydrous ethanol for 3 times. After filtration, they were placed in a glove box for natural evaporation and drying for 30 min to obtain pre-lithiated SiO powders, which were recorded as D1 and D11.

[0161] Comparative Example 2:

[0162] 1) 0.1 mol of benzophenone (BP) was dissolved in 200 ml of dimethyl ether (DME), and the mixture was stirred with magnetic force for 30 min to obtain a mixed solution;

[0163] 2) adding 0.45 mol of lithium flakes with a lithium content greater than 99.5% to the mixed solution, and allowing the solution to stand for 10 minutes to allow the lithium to fully dissolve, thereby forming a lithiated solution;

[0164] 3) 10 g SiO powder (0.22 mol) was added to the lithiation solution and treated by magnetic stirring for 30 min (experimental group 1) and 60 min (experimental group 2). After filtration, the solution was repeatedly washed with anhydrous ethanol for 3 times. After filtration, the solution was placed in a glove box for natural evaporation and drying for 30 min to obtain pre-lithiation SiO powder, which was recorded as D2 and D12.

[0165] Comparative Example 3:

[0166] 1) 0.1 mol of dimethylbiphenyl (4,4-DMBP) was dissolved in 200 ml of dimethyl ether (DME), and the mixture was stirred with magnetic force for 30 min to obtain a mixed solution;

[0167] 2) adding 0.45 mol of lithium flakes with a lithium content greater than 99.5% to the mixed solution, and allowing the solution to stand for 10 minutes to allow the lithium to fully dissolve, thereby forming a lithiated solution;

[0168] 3) 10 g SiO powder (0.22 mol) was added to the lithiation solution and treated by magnetic stirring for 30 min (experimental group 1) and 60 min (experimental group 2). After filtration, the solution was repeatedly washed with anhydrous ethanol for 3 times. After filtration, the solution was placed in a glove box for natural evaporation and drying for 30 min to obtain pre-lithiation SiO powder, which was recorded as D3 and D13.

[0169] Comparative Example 4:

[0170] 1) 0.1 mol of 4,4-difluorobenzophenone (4,4-DFBP) was dissolved in 200 ml of dimethyl ether (DME), and the mixture was stirred with magnetic force for 30 min to obtain a mixed solution;

[0171] 2) adding 0.45 mol of lithium flakes with a lithium content greater than 99.5% to the mixed solution, and allowing the solution to stand for 10 minutes to allow the lithium to fully dissolve, thereby forming a lithiated solution;

[0172] 3) 10 g SiO powder (0.22 mol) was added to the lithiation solution and treated by magnetic stirring for 30 min (experimental group 1) and 60 min (experimental group 2). After filtration, the solution was repeatedly washed with anhydrous ethanol for 3 times. After filtration, the solution was placed in a glove box for natural evaporation and drying for 30 min to obtain pre-lithiation SiO powder, which was recorded as D4 and D14.

[0173] Comparative Example 5:

[0174] The SiO powder was not treated in any way and was recorded as D5.

[0175] Performance test of experimental group 1:

[0176] The negative electrode material samples S1 to S12 prepared in Examples 1 to 12 and the comparative samples D1, D2, D3, D4, and D5 were respectively mixed with sodium carboxymethyl cellulose, styrene-butadiene rubber, conductive graphite (KS-6), and carbon black (SP) in a ratio of 92:2:2:2:2 to prepare slurries, which were uniformly coated on copper foil and dried to form negative electrode sheets, which were assembled into button cells in an argon atmosphere glove box. The diaphragm used was a polypropylene microporous membrane, the electrolyte used was 1 mol / L lithium hexafluorophosphate (the solvent was a mixture of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate), and the counter electrode used was a metal lithium sheet.

[0177] The above 17 groups of batteries were subjected to the first coulombic efficiency test and reversible capacity test on the Blue Power CT2001A battery test system, and the measured test data are shown in Table 1.

[0178] The silicon grains of the 17 SiO powder samples were measured, and the median particle size data of the silicon oxide grains were shown in Table 1.

[0179] Table 1. Sample test data statistics

[0180]

[0181]

[0182] According to the experimental data in Table 1, the first efficiency of the battery in Comparative Example 1 is not improved due to the lack of pre-treatment of metallic lithium and pre-lithium electrode (or powder). Comparative Example 2 uses an aromatic compound (biphenyl) without an R group to treat the lithium source, and its lithium insertion depth is greatly limited. The first efficiency of the battery after pre-lithium treatment is only 78.1%. It can be explained that the aromatic compound without an R group only has a high potential after lithiation, which limits the reaction intensity with SiO. Comparative Examples 3 and 4 use aromatic compounds with R groups to treat the lithium source, and the pre-lithium effect achieves a certain effect. The molar ratio of the aromatic compound with R group to SiO is 0.1:0.22, and the first efficiency is close to 83%. The concentration of the aromatic compound with R group is low, and the lithium insertion efficiency and depth are low.

[0183] In Examples 1 to 12, by matching different combinations of aromatic compounds with R groups, it can be found that there is a certain synergistic effect between different combinations of aromatic compounds with R groups. Different potential difference combinations construct potential gradients and lithium insertion channels, which significantly improve the lithium insertion depth and lithium insertion efficiency. From the first effect data, it can be seen that various combinations can show extremely high lithium insertion capacity. During the low-temperature pre-lithium treatment, the silicon grains basically do not grow, which can avoid the expansion of the electrode caused by grain growth during the pre-lithium treatment, and the falling off of the silicon grains on the electrode. The use of low-temperature lithium can control the lithium particles to not grow at all.

[0184] It can be seen from Examples 1 to 12 that the molar ratio of the Li-aromatic compound to the powder material is 0.1:0.22=0.46. At a low concentration ratio, the first effect of the pre-lithium powder material can reach more than 90% in a short time (30 minutes), which significantly improves the pre-lithium efficiency of the powder material. It can be seen that the composition of aromatic compounds with R groups has a great advantage in lithium insertion, and there is also a certain selectivity between the combinations. There is also a certain optimization selectivity between the mixed solutions formed by different combinations, which makes there a certain difference in the first effect between Examples 1 and 12.

[0185] Performance test of experimental group 2:

[0186] The negative electrode material samples S11 to S22 prepared in Examples 1 to 12 and the comparative samples D11, D12, D13, D14, and D5 were respectively mixed with sodium carboxymethyl cellulose, styrene-butadiene rubber, conductive graphite (KS-6), and carbon black (SP) in a ratio of 92:2:2:2:2 to prepare slurries, which were uniformly coated on copper foil and dried to form negative electrode sheets, which were assembled into button batteries in an argon atmosphere glove box. The diaphragm used was a polypropylene microporous membrane, the electrolyte used was 1 mol / L lithium hexafluorophosphate (the solvent was a mixture of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate), and the counter electrode used was a metal lithium sheet.

[0187] The above 17 groups of batteries were subjected to the first coulombic efficiency test and reversible capacity test on the Blue Power CT2001A battery test system, and the measured test data are shown in Table 2.

[0188] The silicon grains of the 17 SiO powder samples were measured, and the median particle size data of the silicon oxide grains were shown in Table 2.

[0189] Table 2. Sample test data statistics

[0190] sample First effect (%) Reversible capacity (mAh / g) Silicon oxide grains(nm) D11 77.3 1632.1 3.2 D12 78.0 1325.3 3.2 D13 85.7 1320.6 3.2 D14 78.1 1337.1 3.4 D5 76.3 1662.0 3.3 S11 101.3 1420.0 3.4 S12 99.8 1419.3 3.3 S13 95.2 1409.9 3.2 S14 82.3 1419.6 3.2 S15 84.1 1424.7 3.3 S16 93.3 1388.1 3.3 S17 93.0 1376.3 3.2 S18 91.9 1380.9 3.3 S19 81.2 1393.2 3.3 S20 95.9 1420.8 3.4 S21 90.5 1386.1 3.3 S22 83.11 1361.2 3.3

[0191] According to the experimental data in Table 2, after the lithiation time of SiO2 increases from 30 min to 60 min, the first efficiency of the battery is improved after lithiation treatment with the lithiation solution prepared from the aromatic compound monomer or composition having an R group. From the first efficiency data, it can be seen that the material has an extremely high lithium insertion capacity, indicating that the low concentration of the composition of the aromatic compound having an R group has a great lithium insertion advantage.

[0192] According to all the above test data, the aromatic composition composed of aromatic compounds with R groups has greater advantages in solvation pre-lithiation treatment, the material has extremely high lithium insertion capacity, and the first efficiency and capacity of the battery are greatly improved. In addition, low concentrations of aromatic compounds with R groups can reduce the loss of metallic lithium.

[0193] Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the claims. Any technical personnel in this field may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.

Claims

1. A method for preparing a negative electrode material, characterized in that: The method comprises the following steps: Adding a lithium source to a mixed solution containing an aromatic composition and an organic solvent to form a lithiated solution, wherein the lithiated solution includes a Li-aromatic compound, wherein the aromatic composition includes an aromatic compound having an alkane group and an aromatic compound having an ether group; or, an aromatic compound having an alkane group and an aromatic compound having a halogen; or, an aromatic compound having an ether group and an aromatic compound having a halogen; The negative electrode powder material is added into the lithiation solution and dried to obtain the pre-lithiation negative electrode material.

2. The method according to claim 1, characterized in that Possess at least one of the following characteristics (1) to (3): (1) The alkane group includes at least one of -CH3, -C2H5 and -C3H7; (2) The ether group includes at least one of -OCH3, -OCH2CH3 and -OC6H5; (3) The halogen includes at least one of -Cl, -F, -Br and -I.

3. The method according to claim 1, characterized in that The aromatic composition comprises: 10% to 80% by mole of an aromatic compound having an alkane group and 20% to 90% by mole of an aromatic compound having an ether group; or 60% to 95% by mole of an aromatic compound having an alkane group and 5% to 40% by mole of an aromatic compound having a halogen; or The molar proportion of the aromatic compound having an ether group is 60% to 95% and the molar proportion of the aromatic compound having a halogen group is 5% to 40%.

4. The method according to any one of claims 1 to 3, characterized in that Possess at least one of the following features (1) to (2): (1) The organic solvent comprises at least one of dimethyl ether, dimethyl carbonate, tetrahydrofuran, carbonates, toluene, benzene, ether, propylene oxide and ketone solvents; (2) The concentration of the aromatic compound in the mixed solution is 0.2 mol / L to 2.0 mol / L.

5. The method according to any one of claims 1 to 3, characterized in that: Possess at least one of the following features (1) to (8): (1) The lithium source includes at least one of lithium metal and a lithium alloy having a lithium content greater than 40%; (2) the molar ratio of lithium in the lithium source to the aromatic composition is greater than 2; (3) The dissolution time of the lithium source is 5 min to 10 min, and the dissolution temperature of the lithium source is 10° C. to 30° C.; (4) The molar ratio of the Li-aromatic compound to the negative electrode powder material is (0.2-2):1; (5) The negative electrode powder material includes at least one of a silicon-based material, a carbon-based material and a silicon-carbon composite material; (6) The particle size of the negative electrode powder material is less than 50 μm; (7) The drying is carried out under a protective gas, wherein the protective gas comprises at least one of helium, neon, argon, krypton and xenon; (8) The drying time is 15 min to 60 min.

6. The method according to claim 1, characterized in that The method comprises: Adding a lithium source to a mixed solution containing an aromatic composition and an organic solvent to form a lithiated solution, wherein the lithiated solution includes a Li-aromatic compound, wherein the aromatic composition includes an aromatic compound having an alkane group and an aromatic compound having a halogen; Add silicon dioxide into the lithiated solution, stir, filter, and wash with an organic solvent, filter, and dry to obtain a pre-lithiated silicon dioxide material.

7. A negative electrode material, characterized in that: The negative electrode material includes nano-silicon, a silicon-oxygen lithium compound and an aromatic compound, wherein the silicon-oxygen lithium compound includes at least one of Li2Si2O5, Li2SiO3 and Li4SiO4, and the aromatic compound at least partially covers the nano-silicon and the silicon-oxygen lithium compound; The aromatic compounds include aromatic compounds having alkane groups and aromatic compounds having ether groups; or, an aromatic compound having an alkane group and an aromatic compound having a halogen; Or, an aromatic compound having an ether group and an aromatic compound having a halogen.

8. The negative electrode material according to claim 7, characterized in that The negative electrode material has at least one of the following characteristics a to d: a. The median particle size of the negative electrode material is 4.0um~8.0um; b. The specific surface area of ​​the negative electrode material is 1.5m 2 / g~4.2m 2 / g; c. The pH value of the negative electrode material is 10.0~11.5; d. The negative electrode material further comprises a carbon coating layer.

9. The negative electrode material according to claim 7, characterized in that The negative electrode material also includes a carbon coating layer, and the aromatic compound is distributed on the surface of the nano silicon particles, in the pores of the carbon coating layer and on the outer surface of the carbon coating layer.

10. Application of a negative electrode material in a lithium ion battery, characterized in that: The lithium-ion battery comprises a negative electrode plate, a positive electrode plate, a separator and a non-aqueous electrolyte, wherein the negative electrode plate comprises a current collector and a negative electrode material prepared by the method for preparing the negative electrode material according to any one of claims 1 to 6 or the negative electrode material according to any one of claims 7 to 9 coated on the current collector.

Citation Information

Patent Citations

  • Lithium supplementing method of lithium ion battery negative electrode active material

    CN112234160A

  • Long life lithium batteries with stabilized electrodes

    US20060147809A1